Heaven preserve us [large type] - McRae, Cricket (McRae, Cricket. Home crafting mystery, 2008)
After solving the messy mystery of her handyman's lye-induced death, thirty-something Sophie Mae Reyonlds makes preserves by day and answers a crisis hotline by night. What better way to keep a low profile? But during her first shift, she gets a call from a man who is threatening suicide ... and her.